2014
DOI: 10.1186/1472-6963-14-342
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative patient characteristics on the cost-effectiveness of total hip replacement: a cohort study

Abstract: BackgroundTo facilitate the discussion on the increasing number of total hip replacements (THR) and their effectiveness, we apply a joint evaluation of hospital case costs and health outcomes at the patient level to enable comparative effectiveness research (CER) based on the preoperative health state.MethodsIn 2012, 292 patients from a German orthopedic hospital participated in health state evaluation before and 6 months after THR, where health-related quality of life (HRQoL) and disease specific pain and dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Vogl and colleagues found that THR was associated with positive undiscounted incremental costs of €7,730 relative to medical therapy, and reported higher costs among patients with more severe disease. 90 The undiscounted incremental costs of timely THR in a 65 year old in our analysis were instead €2024 in females, and €3,524 in males. The difference with our results is due to Vogl’s assumption that the non-surgical costs in the THR arm were equal to those of the medical arm, whereas we accounted for higher non-surgical healthcare costs in the medical therapy arm than under timely THR, especially after disease progression.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Vogl and colleagues found that THR was associated with positive undiscounted incremental costs of €7,730 relative to medical therapy, and reported higher costs among patients with more severe disease. 90 The undiscounted incremental costs of timely THR in a 65 year old in our analysis were instead €2024 in females, and €3,524 in males. The difference with our results is due to Vogl’s assumption that the non-surgical costs in the THR arm were equal to those of the medical arm, whereas we accounted for higher non-surgical healthcare costs in the medical therapy arm than under timely THR, especially after disease progression.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, we found larger QALY gains for timely than among delayed therapy despite the more severe status of patients at the time of delayed THR and allowance in our analysis for larger pre to post-operative health gains of patients with more severe disease. 48 The reason for the different results between the two studies is that delayed THR arm in our study measured the expected QALY gains at the time the decision between timely, delayed or no surgery is made, whereas the results by disease severity reported by Vogl 90 are calculated at the time patients are operated and therefore, unlike our results, miss the loss in utility during any delay of treatment experienced by the more severe patients.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…15 We recently used this approach to examine the cost structure in hip replacement surgery. 31 The InEK scheme differentiates by cost centers and cost categories (investment costs excluded). Each combination of a cost center and cost category is allocated to an activity-based cost driver; for example, costs of the physicians (cost category) on ICU (cost center) are attributed to individual LTX patients according to their treatment interval at the ICU (activity-based cost driver).…”
Section: Discussionmentioning
confidence: 99%
“…In this version, VAS values were estimated at the population level in previous studies [12,13], but EBVSs have only been developed for Germany, Sweden, and China [10,14,15]. These EVBSs have also been used and tested in a number of chronic diseases [16][17][18][19][20][21] and in elective surgery [22,23]. Meanwhile, a more differentiated version, the EQ-5D-5L, has been developed, covering five problem levels and a total of 3125 health states [24].…”
Section: Introductionmentioning
confidence: 99%